2019
DOI: 10.1016/j.neuroimage.2018.09.077
|View full text |Cite
|
Sign up to set email alerts
|

Community and household-level socioeconomic disadvantage and functional organization of the salience and emotion network in children and adolescents

Abstract: Socioeconomic disadvantage (SED) during childhood has been linked to disparities in physical and mental health. A growing body of research has focused on identifying neurodevelopmental consequences of SED, commonly measured using within-household factors (e.g., household income), to better understand the processes underlying SED-related disparities. These studies suggest that childhood SED has a widespread impact on brain development, altering development of multiple brain regions simultaneously. These finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…In South Korea, community child centers are primarily used by children from vulnerable social groups such as single-parent households, living with grandparents, multicultural children, and low-income families [51]. Our study suggests that the socioeconomic status of the family has an effect on the child’s affect, and these findings are consistent with those of Gellci et al [52].…”
Section: Discussionsupporting
confidence: 90%
“…In South Korea, community child centers are primarily used by children from vulnerable social groups such as single-parent households, living with grandparents, multicultural children, and low-income families [51]. Our study suggests that the socioeconomic status of the family has an effect on the child’s affect, and these findings are consistent with those of Gellci et al [52].…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the sample of children was predominantly Black American, fitting with the participating schools' demographic composition and surrounding neighborhoods. Further, the sample, on average, resided in communities of moderate-to-high distress ( Gellci et al., 2019 ; Marshall et al., 2018 ), estimated using the Distressed Communities Index ( https://eig.org/dci ). However, within-household markers of SES (i.e., parent education) ranged across the sample, with 41% of parents reporting some college or a high school diploma (see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, youth from high-SES neighbourhoods showed a steeper positive relationship between segregation and age during adolescence, such that by their early 20s, they showed greater functional network segregation than youth from low-SES neighbourhoods. Another study of individuals in a similar age range (6-17 years) revealed an interaction between household and neighbourhood SES, such that among youth in low-SES neighbourhoods, higher household SES is associated with greater local functional network segregation (assessed by the clustering coefficient) in the prefrontal cortex 65 . The available evidence is consistent with the hypothesis that higher SES is associated with more protracted functional network development, with youth from high-SES backgrounds showing more widespread connectivity and thus lower segregation early in development, before the rapid development of a more segregated network architecture that continues into adulthood 10,11 .…”
Section: Functional Network Developmentmentioning
confidence: 97%